Erdheim-Chester disease with isolated craniocerebral involvement. (15th April 2013) - Jain, Rajendra Singh; Sannegowda, Raghavendra Bakki; Jain, Rahul; Mathur, Tarun
Abstract : Erdheim-Chester disease (ECD) is a rare non-Langerhans form of histiocytosis with distinctive radiographic and pathological features. Intracranial involvement is further a rarity, usually producing diabetes insipidus or cerebellar-brainstem symptoms. We report a 40-year-old man presenting with recurrent secondarily generalised seizures. An MRI scan of the brain revealed multiple enhancing intracranial masses in frontal, temporal and parietal regions. Biopsy from the left frontotemporal lesion confirmed it to be a rare case of ECD. The patient received a short course of corticosteroids initially and subsequently remained well-controlled on antiepileptic therapy alone. A repeat MRI of his brain showed significant resolution of lesions. Osteolytic lesions in the skull vault were detected during follow-up which also disappeared. Interestingly, there was no involvement of long bones or any other system even after 12 years of follow-up.